Implementasi Pelayanan Pendidikan Agama Kristen dalam Mendukung Pertumbuhan Rohani Jemaat di GKSI Pelita Harapan Lembo Kodi - Wiranto Wiranto; Lisa Sababalat (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This study aims to evaluate the implementation of the Christian Religious Education (PAK) program in supporting the spiritual growth of the congregation at GKSI Pelita Harapan Lembo Kodi. The primary focus is to assess how structured, participatory, and contextual faith development methods can enhance biblical understanding, strengthen spiritual discipline, and encourage active involvement in church-based social ministries. The program was carried out using various methods, including interactive lectures, group discussions, personal spiritual mentoring, and direct community service practices. All activities were consistently implemented throughout the duration of the Community Service Program (PkM). The results indicate that the program had a positive impact on the spiritual lives of the congregation. There was a notable increase in attendance at church events, active participation in discussions and ministry, and tangible changes in spiritual behavior. Congregants demonstrated discipline in personal prayer and regular Bible reading, as well as heightened social concern. The internalization of Christian values began to manifest in their daily lives. the evaluation also identified several challenges, including time constraints and varying levels of biblical understanding among congregants. These findings highlight the need for more flexible and inclusive approaches in faith development. In conclusion, a holistic faith education approach integrating cognitive, affective, and practical dimensions proves effective in forming spiritually mature believers, actively engaged in ministry, and strengthening the church community. These findings provide a solid foundation for churches to design relevant, contextual, and sustainable spiritual development programs.